Advances in Quantum Methods and Applications in Chemistry, Physics, and Biology - Hotokka, Matti.; Brñdas, Erkki J.; Maruani, Jean.; Delgado-Barrio, Gerardo. (Progress in Theoretical Chemistry and Physics, 2013)
Advances in Quantum Methods and Applications in Chemistry, Physics, and Biology includes peer-reviewed contributions based on carefully selected presentations given at the 17th International Workshop on Quantum Systems in Chemistry, Physics, and Biology. New trends and state-of-the-art developments in the quantum theory of atomic and molecular systems, and condensed matter (including biological systems and nanostructures) are described by academics of international distinction.